Characterization of the causative organism of ornamental fish mycobactriosis in Malaysia - Shamsudin, Mad Nasir; Tajima, K.; Kimura, T.; Shariff, M.; Anderson, L. G. (Japanese Society of Fish Pathology, 1990)
The causative organism of fish mycobacteriosis in ornamental fish (goldfish, Carassius auratu and red eyed tetra, Moenkhausia sanctaefilomenae) in Malaysia was characterized by examining biochemical and physiological properties. The organism formed tiny white colonies in less than three days at 30°C on Bacto Lowenstein Medium in complete darkness, but become yellow after exposure to light (photochromogenic). The isolate was an acid-fast, weakly Gram positive rod and the guanine plus cytosine (% G+C) was 62.6. It was confirmed that the isolate belonged to the genus Mycobacterium. The isolate differed in many characteristics from the reference strains of M. chelonei subsp. chelonei and M. chelonei subsp. abscessus, as well as the rapidly growing, photochromogenic M. parafortuitum and M. vaccae cited in the Bergey's Manual of Systematic Bacteriology vol. 2 (1986).